SAT0462 Secukinumab provides sustained pasdas related low disease activity in psoriatic arthritis: 2 year results from the future 2 study. (15th June 2017) - Coates, LC; Gladman, DD; Nash, P; Fitzgerald, O; Kavanaugh, A; Rasouliyan, L; Pricorp, L; Ding, K; Gaillez, C; ,
Abstract : Background: Psoriatic arthritis (PsA) disease activity score (PASDAS) assessing multiple facets of PsA was demonstrated to distinguish treatment effect, perform better in statistical terms than traditional joint-only indices 1 and could be used as a treatment target in clinical trials in PsA. Objectives: Secukinumab provided sustained improvement in the signs and symptoms of PsA over 104 weeks (wks) in the FUTURE 2 study. 2 Here, we report the ability of secukinumab to reach and sustain PASDAS based low disease activity (LDA) up to 104 wks in the FUTURE 2 study using a post-hoc exploratory analysis. Methods: 397 patients (pts) with active PsA were randomised to subcutaneous (s.c.) secukinumab (300mg, 150mg, or 75mg) or placebo (PBO) at baseline (BL), Wks 1, 2, and 3, and every 4 wks (q4w) from Wk 4. PBO nonresponder and responder pts were re-randomised to secukinumab 300 or 150mg s.c. q4w from Wk 16 and 24, respectively. PASDAS is derived from physician's global VAS, patient's global VAS, SF-36 PCS, tender and swollen joints (TJC 68 and SJC 66), Leeds enthesitis count, dactylitis count and CRP level and has cut-points for high disease activity (HDA≥5.4), low disease activity (LDA<3.2) and remission (REM≤1.9). 3 PASDAS was assessed in the overall population and in pts stratified by prior anti-TNF use (naïve/inadequate response [IR]) and disease duration (≤2 years vs. >2 years since diagnosis) and reported using non-mutually exclusive categories at group level and as observed analysis. Secukinumab 75mg data are not reported as this was not considered an effective dose. 2 Results: PASDAS score (mean [SD]) at baseline was 5.9 (0.9), 6.0 (1.0) and 5.8 (1.0) in the secukinumab 300mg, 150mg and PBO groups. In the overall population at Wk 16, PASDAS LDA was achieved in 37/96 (38.5%) and 34/99 (34.3%) of pts, treated with secukinumab 300mg and 150mg, respectively; vs. 14/87 (16.1%) with PBO. A high proportion of pts treated with secukinumab 300 and 150mg achieved LDA (49/83 [59.0%] and 38/77 [49.4%], respectively) at Wk 104. The proportion of pts achieving PASDAS LDA and remaining in HDA at Wks 16 and 104 by anti-TNFα status and by disease duration (≤2 years vs. >2 years) for secukinumab 300 and 150mg is reported in the figure. Conclusions: A higher proportion of secukinumab-treated pts at Wk 16 achieved PASDAS LDA than PBO, with LDA sustained at group level at Wk 104. Discriminatory effect of PASDAS was consistent with that previously reported in the GRACE project. 4 A higher proportion of anti–TNFα-naïve pts treated with secukinumab achieved and sustained PASDAS LDA than anti–TNFα-IR pts whereas similar proportion of pts treated with secukinumab achieved PASDAS LDA irrespective of time since diagnosis (≤2 years vs. >2 years). References: Helliwell PS and Kavanaugh A. Arth Care and Res. 2014;66:749–56. McInnes IB et al, Arthritis Rheumatol. 2016;68 (suppl 10). Coates LC and Helliwell PS, J Rheumatol. 2016;43:371–5. Helliwell PS et al, Ann Rheum Dis. 2013;72:986–91. Disclosure of Interest: L. Coates Grant/research support from: Abbvie, Janssen, Consultant for: Abbvie, BMS, Celgene, Pfizer, UCB, MSD, Novartis, Lilly, Janssen, Sun Pharma, D. Gladman Grant/research support from: Amgen, AbbVie, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer and UCB, P. Nash Grant/research support from: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, Consultant for: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, Speakers bureau: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, O. Fitzgerald Grant/research support from: Bristol-Myers Squibb, Roche, Abbott, Consultant for: Bristol-Myers Squibb, Roche, Abbott, A. Kavanaugh Consultant for: Novartis, L. Rasouliyan Consultant for: Novartis through employment at RTI Health Solutions, Employee of: RTI Health Solutions, L. Pricorp Shareholder of: Novartis, Employee of: Novartis, K. Ding Shareholder of: Novartis, Employee of: Novartis, C. Gaillez Shareholder of: Novartis, BMS, Employee of: Novartis